Blockchain: a transformation in the tax and accounting sector - Alencar, Levi Carmo (2022)
This work aims to identify the main impacts of Blockchain as a tool in the tax and accounting sector, as well as possible transformations in the sectors. The present work has an exploratory approach, based on a bibliographic study, from which it was identified that Blockchain is a revolutionary technology with the potential to reach the business world. The results show that US$ 1.4 billion has already been invested in technology in the last three years. The number of investments in this technology is increasing, since Blockchain is a technology of shared information records, it is a shared ledger that allows greater transparency in the financial transactions of organizations. In this context, the tax and accounting sector will be transformed, since the information contained in this technology is updated in real time and cannot be deleted, making the information more transparent. In this way, the use of Blockchain should enhance the entrepreneur's available time in his business, in addition to providing a way to safely and efficiently create an inviolable record of activity. However, several countries do not have regulations in the legal environment for this technology.